Locally Embedded Civil Society Organizations and Public Diplomacy: the Advocacy Roles of the “Mothers of Srebrenica” in Promoting a Culture of Remembrance - Hasić, Jasmin; Karabegović, Dženeta; Turković, Bisera (Studies of Transition States and Societies, 2021)
Increasingly, non-state actors exercise unofficial forms of influence within international affairs. Analyzing the actions and platforms in which they operate offers a broader perspective on their influence within diplomatic spheres traditionally occupied by state actors. This paper explores the relationship between victim-oriented advocacy roles taken by the NGO ‘Mothers of Srebrenica’ and the resulting formulation of a ‘culture of remembrance’ as an unofficial part of Bosnia and Herzegovina’s cultural and public diplomacy portfolio. We examine the Mothers’ advocacy work in promoting genocide remembrance and fighting genocide denial within the country’s foreign policy agency framework. We scrutinize under which circumstances their advocacy shapes or is formulated in parallel with official state diplomacy. We trace three types of advocacy engagement and discuss the influence in contributing to the country’s cultural and public diplomacy. This analysis contributes to scholarship on the influence of non-state actors in public diplomacy by examining the role of advocacy organizations on local, regional, and global levels and expanding the scholarship about the intersection of non-state actors and cultural and public diplomacy to include states undergoing transition, particularly post-conflict states.